2018
DOI: 10.1177/1553350618785270
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Hematoma Evacuation for Acute Subdural Hematoma in the Elderly: A Preliminary Study

Abstract: Our surgical procedure is safe and effective when performed with strict operative indications. Endoscopic surgery for ASDH in elderly adults may be an alternative to a large craniotomy in simple-type hematomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The median operative time in our study of 107 minutes was similar to that reported in the previous series of endoscopic-assisted subdural hematoma evacuations found in the literature [19][20][21]23,24]. There will definitely be a learning curve for neurosurgeons unfamiliar with the use of the endoscope in their daily practice that will impact the operative time at first, but as with any other newly learned technique, continuous use will likely improve surgical procedure duration.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The median operative time in our study of 107 minutes was similar to that reported in the previous series of endoscopic-assisted subdural hematoma evacuations found in the literature [19][20][21]23,24]. There will definitely be a learning curve for neurosurgeons unfamiliar with the use of the endoscope in their daily practice that will impact the operative time at first, but as with any other newly learned technique, continuous use will likely improve surgical procedure duration.…”
Section: Discussionsupporting
confidence: 82%
“…There will definitely be a learning curve for neurosurgeons unfamiliar with the use of the endoscope in their daily practice that will impact the operative time at first, but as with any other newly learned technique, continuous use will likely improve surgical procedure duration. The operative time for standard craniotomy/craniectomy for acute subdural hematoma evacuation reported in the literature has a wide range of reported times as short as 49 minutes to longer than two hours [21,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ere have been increasing reports of the use of endoscopic hematoma evacuation for ASDH in the elderly. [1][2][3][4][5][7][8][9][10][11][12][13][14] In a recent scoping review, mortality rates ranged between 0% and 40%, whereas the rate of favorable outcomes ranged between 26.7% and 96.4%. [13] Rebleeding was the most commonly reported complication, with a prevalence ranging between 0% and 13%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports on endoscopic hematoma removal with small craniotomy for ASDH have been increasing. [1][2][3][4][5][7][8][9][10][11][12][13][14] is minimally invasive surgery could compensate for the disadvantages of craniotomy and craniectomy. In this study, we report a case series of nine patients with ASDH who underwent endoscopic hematoma removal with small craniotomy under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%